An Analysis of English for Specific Purposes among University Students - Edita Bekteshi; Brikena Xhaferi (Educational Process: International Journal)
The study gives an account of English for Specific Purposes (ESP) within the engineering field, students’ willingness to learn professional English vocabulary, and ESP issues related to Higher Education Institutions (HEIs). The study investigates students´ need to learn English through data analyzed in a descriptive and exploratory study, focusing on the students’ perceptions about ESP based on their English language level and ESP learning practices, and its integration within HEIs. A questionnaire was completed by 239 university students and 16 face-to-face interviews were held. The collected data were subjected to SPSS statistical analysis and the results were then analyzed and discussed. The study identified that university students can acquire professional vocabulary in English language classes, providing high levels of stimulus for future job opportunities in the engineering field. The highest priority for the students was learning ESP for employment purposes, with the primary focus being the enhancement of their communicative skills.